UTILIZING GADGET BASED INTERNET APPROACH DURING THE PANDEMIC TO IMPROVE STUDENTS’ BAHASA INDONESIA LEARNING OUTCOMES AT GRADE IV OF SD NEGERI 10 BAGAN PUNAK KECAMATAN BANGKO - Dahniar Dahniar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aimed to improve the students’ learning outcomes at fourth grade of SDN 010 Bagan Punak, Kecamatan Bangko, through a gadget-based internet use approach. The subjects of this study consisted of 20 students. This research was classroom action research with the aim of improving the learning outcomes and learning activities. The results of the research found that the initial data on the average score of students’ learning outcomes was only 60, meaning that it had not yet reached the completeness of the learning outcomes. Then, after learning to use the gadget-based internet with zoom media from cycle I to cycle II, students’ learning outcomes increased from the beginning of learning when using gadget-based internet in learning Bahasa Indonesia and continued to increase in each cycle. This was evidence of the success of using internet in improving student learning outcomes. In the first cycle, there was a good increase in which the average value of students’ learning outcomes as a whole was 74.6compared to the initial data which was only 60. The number of students with complete learning outcomes were 15 of the 20 students who took the learning outcomes test. it indicated around 75% of the fourth grade students at SDN 010 Bagan Punak, Kecamatan Bangko Then, it was proceeded to the second cycle in which the average of students’ learning outcomes also experienced a good increase. The students’ learning outcomes in the second cycle was 81.8 meaning that has achieved good completeness. There were about 18 students from 20 students who took the learning outcomes test completed the test, meaning that around 90% of fourth grade students at SDN 010 Bagan Punak, Kecamatan Bangko.